2010
DOI: 10.1159/000320245
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Arterial Cardiovascular Diseases in Patients with Multiple Sclerosis: A Population-Based Cohort Study

Abstract: Background: Patients with multiple sclerosis (MS) may have a higher risk of cardiovascular diseases (CVD) than the general population, but data are limited. Methods: We conducted a population-based cohort study involving Danish citizens diagnosed with MS (n = 13,963) from 1977 to 2006 and an age- and sex-matched population cohort (n = 66,407) using data on MS, arterial CVD and comorbidity from the Danish National Registry of Patients. We calculated the risk of arterial CVD for all subjects and computed adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
180
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(194 citation statements)
references
References 90 publications
10
180
1
3
Order By: Relevance
“…For practical reasons we also compared medical records to administrative data for the 1- to 5-year period ending in fiscal year 2005/06, rather than from 1984 onward, potentially contributing to some disagreement between data sources. We have not developed methods to assess all of the comorbidities which potentially are relevant to persons with MS. Of particular relevance to pursue may be ischemic heart disease and stroke, based on work by Danish investigators [33], as well as mental comorbidities which are known to be common in MS but remain understudied at the population level [34]. We could not examine the impact of risk factors on the prevalence of comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…For practical reasons we also compared medical records to administrative data for the 1- to 5-year period ending in fiscal year 2005/06, rather than from 1984 onward, potentially contributing to some disagreement between data sources. We have not developed methods to assess all of the comorbidities which potentially are relevant to persons with MS. Of particular relevance to pursue may be ischemic heart disease and stroke, based on work by Danish investigators [33], as well as mental comorbidities which are known to be common in MS but remain understudied at the population level [34]. We could not examine the impact of risk factors on the prevalence of comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The precise etiology of the disease is still unknown, although epidemiological data indicate that genetic and environmental factors are important [2]. Despite data are still scarce, studies point to an increased cardiovascular risk (CVR) in patients with MS, at least when compared with individuals of similar age [3][4][5]. MS patients exhibit autonomic dysfunc-tion [6], increased blood pressure and tachycardia [7], ventricular disturbances [8] and impairment of the balance between vasoconstrictors and vasodilators, such as prostaglandins and nitric oxide (NO) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have assessed cardiac comorbidities in patients with MS, the objective of these previous studies was to compare the frequency relative to the general population, and their findings are largely mixed. 12 Regardless of the relative risk of cardiac comorbidities associated with MS compared with the general population, our findings show overlap in these conditions, and ours is the only study to examine the specific cardiac comorbidities in the fingolimod prescribing information within 1 study.…”
Section: Frequency Of CV Diagnoses In Ms With Cardiac Condition Cohormentioning
confidence: 60%
“…Three studies using hospital discharge records have assessed the risk of cardiac diseases in patients with MS relative to patients without MS. [12][13][14] The most recent of these studies, conducted by Christiansen et al (2010), utilized the Danish National Registry of Patients and reported an increased adjusted 1-year incidence rate ratio (IRR) of MI (IRR = 1.84, 95% confidence interval [CI] 1.28, 2.65), stroke (IRR = 1.95, 95% CI 1.42, 2.71), and heart failure (IRR = 1.92, 95% CI 1.27, 2.90). 12 But, Allen et al (2008) reported a reduced risk of MI (odds ratio [OR] = 0.78, 95% CI 0.64, 0.96) and ischemic heart disease (OR = 0.58, 95% CI 0.51, 0.66) but an increased risk of stroke (OR = 1.66, 95% CI 1.33, 2.09) in an urban U.S. setting. 13 Finally, Fleming et al (1994) reported a significantly reduced likelihood (P < 0.05) of MI, heart failure, angina, and cardiovascular disease among discharges for elderly patients insured by Medicare in the United States.…”
mentioning
confidence: 99%